Elaboración del Papel Artesanal a Base de los Residuos Vegetales de los Tallos de Maíz (Zea Mays L) y Cáscaras de Platano (Musa Paradisiaca L) Ulilizando los Métodos Químicos de Jayme-Wise, Kurshner Y Hoffner” - Andy Huatatoca, Lucia Salomé (2020)
Paper is one of the essential materials in our activities. Its primary source is wood because of its high content of cellulosic fibers. In this research, a chemical process of Jayme-Wise, Kurshner, and Hoffner method is used, with the purpose of elaborate craft paper based on banana peels and corn stalks. Physical-chemical analysis of the raw material was performed, such as moisture, ash, ethereal extract, fiber, lignin, holocellulose, and cellulose. The amount of cellulose in corn stalks was obtained 63.66% and 51.33% in banana peels, optimal for craft paper with dour units: two with Sodium Hydroxide in the Jayme-Wise method (CP1-MJW and TM1-MJW), same as Sodium Sulfite for the Kushner and Hoffner method (CP2-MKH and TM2-MKH). For the final product data, a statistical program was applied Infostat Version 6.2 Argentines and spreadsheet in the analysis of variance and Tukey tests; for each method in the elaboration craft paper. The unit of craft paper TM1-MJW (Corn stalks with the Jayme-Wise method), has better characteristics with the moisture of 6.42%, ash 4.53%, weigh 45.82 g/m2, thickness 0.06 mm, porosity 17.97%, explosion resistance 54.86 kPa.m2/g, tensile strength 129.36 Kn, tear-resistance 301.59 Mn, these results were compared with the TAPPI Standard and INEN Standard, used as paper bags for storing dry food, seeds, and other products.